CAR-T cell therapy clinical trials: global progress, challenges, and future directions from ClinicalTrials.gov insights - Cao, Li-Ya; Zhao, Yue; Chen, Yang; Ma, Pan; Xie, Jiang-Chuan; Pan, Xin-Mei; Zhang, Xin; Chen, Yong-Chuan; Wang, Qian; Xie, Lin-Li (Frontiers in Immunology, 2025)
Chimeric antigen receptor T (CAR-T) cell therapy has undergone vigorous development in recent years, yet it still faces significant challenges and difficulties in its clinical application and further development. A systematic synthesis of global trends in CAR-T clinical trials is essential to identify knowledge gaps, optimize treatment strategies, and guide future research directions. This review analyzed 1,580 CAR-T clinical trials registered at ClinicalTrials.gov as of April 2024, and extracted characteristic data in multiple dimensions, including target specificity, treatment indication, and development stage etc. The transparency of trial outcomes was assessed by validation with articles published in PubMed/Google Scholar. Additionally, it is complemented by investigator surveys assessing to barriers to CAR-T development, prospects, and recommendations.